Nutrition, biochemical, communication and consciousness - Massimo Cocchi (Publiediting, 2008)
This writing seeks to interpret the relationship between the metaphysical aspects of the mind and consciousness with the biological aspects. In particular it wants to stress the need of seeking a harmonious merger between subjective assessment of the psyche and the characterization of the biological psychiatric disorder. A great time for research is spent today to identify those mechanisms that are considered still unknown, not yet discovered, but ready to be caught with some great intuition. The point is to understand the mechanism of signalling, gene expression and the levels, perhaps even more sub microscopic than those perceived now, of the cell communication. What events may be determined as consequence of the gradual modification of the membrane function? A recent convergence on this issue led to the creation of a very suggestive working hypothesis that is, the occurrence of a biological continuum between the fatty acid composition of cell membranes, protein Gs alpha, tubulin and state of consciousness.